2018
DOI: 10.1002/cre2.141
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cone beam computed tomography image quality in implant dentistry

Abstract: This study was conducted to optimize the cone beam computed tomography image quality in implant dentistry using both clinical and quantitative image quality evaluation with measurement of the radiation dose. A natural bone human skull phantom and an image quality phantom were used to evaluate the images produced after changing the exposure parameters (kVp and mA). A 10 × 5 cm2 field of view was selected for average adult. Five scans were taken with varying kVp (70–90 kVp) first at fixed 4 mA. After assessment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Nine studies were excluded for not meeting the eligibility criteria. Sixteen studies were selected for full-text reading, after which 7 studies were excluded because they dealt with topics related to artifact reduction, the evaluation of peri-implant tissue, and comparisons between the implant radiation dose of CBCT and MSCT, 11 12 13 14 15 16 17 yielding a final total of 9 selected articles. 18 19 20 21 22 23 24 25 26 …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were excluded for not meeting the eligibility criteria. Sixteen studies were selected for full-text reading, after which 7 studies were excluded because they dealt with topics related to artifact reduction, the evaluation of peri-implant tissue, and comparisons between the implant radiation dose of CBCT and MSCT, 11 12 13 14 15 16 17 yielding a final total of 9 selected articles. 18 19 20 21 22 23 24 25 26 …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, by carrying out the investigations using two commercial CBCT scanners, an analysis of whether the threshold level of objective image quality for this specific diagnostic task could be transferred to a different scanner was carried out. Protocols achieving significant dose reductions for specific dental diagnostic tasks have been established, [11][12][13][14][15] involving dose measurement, objective and subjective assessment, but not in an endodontic context and none of these has investigated the transferability of objective image quality measurements between scanners. Additionally, this study also examined the impact of anatomy complexity on establishing a threshold dose for this diagnostic task and the effect of operator experience on diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…3,9 The pertinence of employing low dose protocols has recently been highlighted, 10 with protocols achieving significant dose reductions suggested in the dental disciplines of paediatric dentistry, 11 orthodontics, 12 tooth autotransplantation (TAT), 13 periodontology 14 and implant dentistry. 15 In the process of optimisation, both the acceptable clinical level of the image quality and the radiation dose may differ according to diagnostic tasks. 16 Although such studies have provided evidence to assist in optimisation efforts for particular scanner models used, there is no evidence that the objective image quality measurements can be transferred to a different manufacturer's CBCT equipment or even to different models from the same manufacturer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocols (n = 10) tested in this study were part of a list of pre-established options defined by i-CAT manufacturer. Other studies designed to assess image quality as function of the device setting found out that optimization was feasible by reducing the exposure/dose below the one established by the manufacturer as default (Dawood et al, 2012;Alawaji et al, 2018).…”
Section: Discussionmentioning
confidence: 99%